Technical report - Maddila, Chandra; Agrawal, Apoorva; Zimmermann, Tom; Forsgren, Nicole; Herzig, Kim; Deursen, Arie van (Microsoft, 2021)
This technical report includes supplemental materials for the paper "Nalanda: A Large-Scale Socio-Technical Graph of Entities and Relationships in Software Development Environment".